Transitional Justice, Recognition, and Authoritative Power - Anika Oettler (German Institute of Global and Area Studies (GIGA), 2017)
The legitimacy of transitional justice currently derives from the contribution it makes to the recognition of victims. Adding the aspect of authoritative power to ongoing debates on transitional justice, however, could significantly alter our views on recognition. Recognition is widely believed to be key to overcoming traumatic experiences. At the same time, however, it strengthens authoritative power. Seeking a more nuanced understanding of the recognition-power nexus, the paper provides a rough and critical account of various understandings of recognition and power on the part of authors such as Honneth, Fraser, Bertram and Celikates, Ikäheimo, Arendt, Foucault, Popitz, and Bourdieu. It then examines how these theoretical approaches intersect and speak to each other. To see recognition as a reciprocal interaction sensitive to power relations is to pave the way for a power-sensitive turn in current debates on victim-centred transitional justice. Multidirectional relationships of power exist, with varying forms of coercion, resistance, and struggle. This insight corresponds with the observation, seen from the other perspective, that truth and recognition are inside power. Placing theoretical approaches to power and recognition side by side has strong implications for politics. The paper therefore applies these theoretical insights to the Colombian peace process, showing the potential and pitfalls of putting recognition into practice.
Keywords: 300; transitional justice; recognition; power; victims; Colombia